Global Britain and Neo-colonialism in Africa Brexit, 'Development' and Coloniality - Langan, Mark. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Through the lens of neo-colonialism and global coloniality, the text revitalises the conventional debates on the logic of the UK's interests in Africa, amidst the reality of Brexit and the resurgence of the 'new scramble' for Africa. Mark Langan interrogates the 'celebrated' conversations around Global Britain and British exceptionalism." - Dr Adeoye O. Akinola, University of Johannesburg "With an exceptionally in-depth examination of key geopolitical issues such as trade, aid, development finance and security, Langan uncovers how the same old colonial interventions and political rhetoric with racist undertones are being refashioned to perpetuate an emergent Empire 2.0." - Dr Nathan Andrews, McMaster University "Mark Langan offers a powerful critique... [the text] sheds light on the neo-colonial nature of these [Africa-UK] relations, but also highlights the ability of Africans to resist the 'Global Britain' project." - Professor Mehdi Boussebaa, University of Glasgow This book examines the implications of Brexit for Africa-UK relations amid a 'new scramble' for the continent. Engaging Nkrumah on neo-colonialism and recent scholarship on global coloniality, Langan here underscores concerns that Brexit was fuelled by an imperial romanticism that now gives rise to a Global Britain project involving the perpetration of 'Empire 2.0' in Africa. In this context, he examines UK elites' pursuit of Brexit trade deals and the 'development' consequences of premature market opening. Throughout its chapters, this work assesses strategic usages of UK aid monies in terms of economic leverage and the externalisation of migration and highlights the impact of UK development finance and corporate activities for the health and wellbeing of workers and host communities. Significantly, Langan explores the UK's pursuit of security interests and human rights criticisms and concludes by highlighting African agency to resist the Global Britain project amid the fragility of the British state itself. Mark Langan is Senior Lecturer in International Political Economy at King's College London, UK. He is also the author of Neo-Colonialism and the Poverty of 'Development' in Africa (Palgrave Macmillan, 2018). .
Chapter 1: Empire 2.0: critical perspectives on Brexit -- Chapter 2: The Commonwealth and neo-colonial discourse in Africa-UK ties -- Chapter 3: British aid and economic prerogatives in Africa: the role of DFID -- Chapter 4: 'Global Britain' and Africa-UK trade relations -- Chapter 5: UK corporations and a 'new scramble' for Africa after Brexit: oil, minerals and land -- Chapter 6: The CDC group and UK private finance in Africa -- Chapter 7: State security and the arms industry in Africa-UK relations.-Chapter 8: Brexit and the future of Africa-UK relations.
Keywords: Africa -- Politics and government; Political science; Economic development; African Politics; Political Science; Development Studies; Development Studies; Development Studies